Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Corrigendum to ‘Hypoxia-driven ferroptosis escape mediates lung injury induced by nickel-refining fumes via oxygen-sensing signaling PHD1/HIF-1α’ [Environ. Pollut. 386 (2025) 127205] - Wenxue Yao; Qianqian Sun; Ruize Wu; Zhiwei Xu; Junjie Lv; Hannong Yv; Hongqing Qi; Weiyang Liu; Yue Wang; Yonghui Wu (Environmental Pollution, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Hypoxia-driven ferroptosis escape mediates lung injury induced by nickel-refining fumes via oxygen-sensing signaling PHD1/HIF-1α - Wenxue Yao; Qianqian Sun; Ruize Wu; Zhiwei Xu; Junjie Lv; Hannong Yv; Hongqing Qi; Weiyang Liu; Yue Wang; Yonghui Wu (Environmental Pollution, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Identification of rebar-cutting status based on shield machine vibration during excavation through diaphragm walls - Jiacheng Sun; Shaoming Liao; Mengbo Liu; Junzuo He; Yingbin Liu; Ruize Sun; Zhansheng Wang (Tunnelling and Underground Space Technology, 2025)

Characterization of the marine medaka AHRs and the comparison with those of Japanese medaka in response to dioxin and additional AHR ligands - Wanglong Zhang; Yanjiao Zong; Ruize Sun; Zhenhong Xue; Wenhui Wan; Anran Ren; Yongchao Ma; Wenjing Tian; Renjun Wang (Aquatic Toxicology, 2025)

Estimating the decadal-scale climate predictability limit using nonlinear local Lyapunov exponent with optimal local dynamic analogues - Ruize Li; Jianping Li; Zhaolu Hou; Ruipeng Sun; Shixin Zhen; Houbin Song (Climate Dynamics, 2025)

Research on effective mercury removal from flue gas over Cl/Br/I/O modified adsorbents at ultra-low temperature - Lingxuan Chen; Ruize Sun; Guangqian Luo; Tong Sun; Li Wang; Leicong Liang; Yulu Zhang; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Decoupling the influence of NOx in flue gas on the application of nano-amorphous selenium for mercury removal - Li Wang; Yu Li; Ruize Sun; Renjie Zou; Yongda Huang; Mingyu Yu; Jing Liu; Guangqian Luo; Hong Yao (Science of The Total Environment, 2024)

Influence of low-temperature pyrolysis pretreatment on the co-combustion performance of coal and waste polyvinyl chloride/tire - Mengli Zhou; Yang Xu; Guangqian Luo; Ruize Sun; Renjie Zou; Chunhui Sun; Xian Li; Hong Yao (Fuel, 2024)

Research on mercury re-release model in wet flue gas desulfurization (WFGD) in coal-fired power plants - Ruize Sun; Mingyu Yu; Guangqian Luo; Li Wang; Mengli Zhou; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2024)

Effect of the main properties of membrane materials on denitrification of hydrogen-based membrane biofilm reactors (H2-MBfRs) - Yinghui Zhang; Kun Dong; Meng Zhang; Xiaofei Wang; Xuehong Zhang; Dunqiu Wang; Ruize Sun; Haixiang Li; Wenjie Zhang (Journal of Water Process Engineering, 2024)

Experimental and numerical study on NOx reduction from NH3/DME/air flame using fuel staging method - Mingyu Yu; Guangqian Luo; Ruize Sun; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Ammonia partial cracking over low-cost Ni catalysts for enhancing combustion - Mingyu Yu; Ruize Sun; Guangqian Luo; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Influence of the preceding August-September-October tropical cyclones over the Western North Pacific on the following spring sea ice in the Beaufort Sea: the bridging role of El Niño - Dingjia Ye; Jianping Li; Fei Huang; Ruipeng Sun; Xinxin Tang; Ruize Li (Climate Dynamics, 2024)

Experimental and theoretical study on recovered nano amorphous selenium as efficient adsorbents for mercury capture from flue gas - Li Wang; Yu Li; Ruize Sun; Renjie Zou; Yongda Huang; Guangqian Luo; Hong Yao (Journal of Cleaner Production, 2024)

Insight into the influence of environmental factors on selenite removal from desulfurization wastewater by NZVI@AC: An experimental and theoretical study - Li Wang; Yu Li; Renjie Zou; Ruize Sun; Hong Tian; Guangqian Luo; Hong Yao (Journal of Water Process Engineering, 2024)

Plasma-assisted synthesis of nano-sulfur adsorbent for efficient removal of mercury from flue gas - Ruize Sun; Guangqian Luo; Mingyu Yu; Li Wang; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2023)

Theoretical and experimental study for the transient behavior of a linear compressor during pulse tube cryocooler cool down process - Bo Wang; Ruize Li; Yijun Chao; Changpei Zhuang; Qinyu Zhao; Shuze Sun; Chunjie Yan; Zhihua Gan (International Journal of Refrigeration, 2023)

Extreme rainfall in Northern China in September 2021 tied to air–sea multi-factors - Yue Sun; Jianping Li; Hao Wang; Ruize Li; Xinxin Tang (Climate Dynamics, 2023)
The September rainfall over Northern China (NC) in 2021 was the heaviest since 1961 and had unprecedented socioeconomic impacts. Holding the hypothesis that the drivers of extreme climate events usually contain extreme factors, we firstly propose the Ranking Attribution Method (RAM) to find the possible air–sea multi-factors responsible for this rainfall event. Via the atmospheric bridges of zonal-vertical circulation and Rossby wave energy propagation, the remote factors of warm sea surface temperature anomalies (SSTA) over the tropical Atlantic, cold SSTA over the tropical Pacific, Southern Annular Mode-like pattern in the Southern Hemisphere and North Pacific Oscillation-like pattern in the Northern Hemisphere jointly strengthened the Maritime Continent (MC) convection and Indian monsoon (IM). Through meridional-vertical circulation, the intensified MC convection enhanced the subtropical high over southern China and induced ascending motion over NC . The local factor of extreme air acceleration in the east Asian upper-level jet entrance region further anchored the location of the southwest-northeast rain belt. The strengthened IM and subtropical high over southern China induced considerable moisture transport to the rain belt via two moisture channels. The combined effect of these extreme dynamic and moisture conditions formed this unprecedented rainfall event. This study suggests that the RAM can effectively reveal the factors that contributed to this extreme rainfall event, which could provide a new pathway for a better understanding of extreme climate events.